Kidney melanosis associated with a novel HSP-1 Hermansky-Pudlak oculocutaneous albinism mutation: a case report - Alaa A. Ali; Zana Sidiq M. Saleem; Shakir S. Jabali; Nashwan M. R. Ibrahim; Michael D. Hughson (BMC Nephrology)
Abstract Introduction Melanin deposition in the kidney is rare and appears limited to the conditions of oculocutaneous albinism and malignant melanoma with melanuria. Melanin is generally an insoluble polymer, and it is curious how people with albinism who have little or no skin pigmentation can secrete melanin into the bloodstream, have it pass through the glomerular filtration barrier, and be absorbed by renal tubules. Methods The concentration and solubility of melanin were analyzed in kidney tissue and urine of a renal transplant donor who had a pre-nephrectomy biopsy performed on a black kidney. Genetic testing of a donor blood sample found a novel homozygous Hermansky-Pudlak syndrome (HPS) HPS1 mutation (c.70G > T; p.Glu24Ter). Melanin was extracted from a 24-hour urine collection, and tissue and urine melanin concentrations were determined by spectrophotometry. Results In the kidney, non-melanosomal melanin was deposited as granules in the proximal tubular epithelium and as large aggregates within macrophages in renal tubular lumens. The kidney melanin concentration was 2 mg/g of tissue. Urine melanin was mainly water-soluble, with an excretion of eumelanin that is within a reported normal range. Conclusions Water-soluble melanin was excreted in the urine of a kidney donor with a novel HSP1 mutation predicted to produce a truncated protein. This resulted in melanin pigmentation of a kidney transplanted into a normally pigmented sibling. Donor and recipient are healthy 3 years after the transplant. Nevertheless, HSP can be associated with kidney, colon, and lung pathology, and the long-term outlook for the recipient kidney and donor’s health is uncertain.